Polypharmacy and Mental Health Issues in the Senior Hemodialysis Patient - Knehtl, Maša; Petreski, Tadej; Piko, Nejc; Ekart, Robert; Bevc, Sebastjan (Frontiers in Psychiatry, 2022)
Hemodialysis (HD) is the most common method of chronic kidney failure (CKF) treatment, with 65% of European patients with CKF receiving HD in 2018. Regular two to three HD sessions weekly severely lower their quality of life, resulting in a higher incidence of depression and anxiety, which is present in one third to one half of these patients. Additionally, the age of patients receiving HD is increasing with better treatment and care, resulting in more cognitive impairment being uncovered. Lastly, patients with other mental health issues can also develop CKF during their life with need for kidney replacement therapy (KRT). All these conditions need to receive adequate care, which often means prescribing psychotropic medications. Importantly, many of these drugs are eliminated through the kidneys, which results in altered pharmacokinetics when patients receive KRT. This narrative review will focus on common issues and medications of CKF patients, their comorbidities, mental health issues, use of psychotropic medications and their altered pharmacokinetics when used in HD, polypharmacy, and drug interactions, as well as deprescribing algorithms developed for these patients.